2023
DOI: 10.1007/s00027-023-00944-0
|View full text |Cite|
|
Sign up to set email alerts
|

Ecological effects of mosquito control with Bti: evidence for shifts in the trophic structure of soil- and ground-based food webs

Abstract: The microbial control agent Bacillus thuringiensis var. israelensis (Bti) has been successfully used worldwide to reduce abundances of biting Nematocera (Diptera), often with little direct impact on non-target organisms observed. However, the potential for additional indirect effects on other ecosystem properties, including on trophic linkages within food webs, is poorly known. We investigated the effects of multiple-year mosquito control treatments using the Bti product VectoBac®-G on the stable isotope compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…However, recent investigations (e.g. Gutierrez-Villagomez et McKie et al, 2023) revealed that Bti can have implications on the trophic structure in aquatic ecosystems, potentially affecting amphibians. This highlights the importance of further research on indirect effects of Bti on aquatic food webs.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent investigations (e.g. Gutierrez-Villagomez et McKie et al, 2023) revealed that Bti can have implications on the trophic structure in aquatic ecosystems, potentially affecting amphibians. This highlights the importance of further research on indirect effects of Bti on aquatic food webs.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus thuringiensis var-israelensis (Bti) is one of these insect bio-insecticides" [12]. "Control of mosquitoes using Bti has a particularly strong potential to affect ground-based and soil-based food webs" [13].…”
Section: Introductionmentioning
confidence: 99%